Optimisation of the performance of neural network based pattern recognition classifiers with distributed systems - Türkoglu, I; Arslan, A (Ieee Computer Soc, 2001)
In this study, a new algorithm with distributed systems is proposed in order to optimise the structure of the classifiers, which have a great importance in pattern recognition. The algorithm is applied to a multi layer neural network classifier which uses the rule of back propagation learning. The long process period is shortened and expected high operation speed is achieved in pattern recognition by minimizing the hardware realization of the classifier.
8th International Conference on Parallel and Distributed Systems (ICPADS 2001) -- JUN 26-29, 2001 -- KYONGJU CITY, SOUTH KOREA
Keywords: Algorithm